Success Drivers for Independent Feature Filmmaking in South Africa - Heatlie, Damon (University of the Witwatersrand, Johannesburg, 2011)
This qualitative research addresses the central research question ‐ why is the South African feature film industry uncompetitive, and what are the key drivers for producing profitable films in the South African context? The central conceptual framework used is value chain analysis. The study limits its scope to focusing specifically on the development and distribution stages of the independent feature film value chain. The study commences by investigating the historic poor performance of South African films, which typically were not able to recoup costs and move into profitability. The study interrogates the critical role of the independent film producer as a ‘creative entrepreneur’ and looks at examples of successful film industry development in other emerging economies. The research then examines what international research indicates as success factors at the development stage, followed by an exploration of the rapidly changing digital landscape of film distribution and its associated opportunities. The empirical research component comprises of the analysis of semi-‐structured expert interviews with 12 industry stakeholders – producers, distributors and funder‐investors involved in feature filmmaking in South Africa. The data analysis involved thematic encoding, a reduction of 10 open–ended questions to four key thematic domains that presented in the findings: ‘understanding the market’, ‘finding a business model’, ‘government support’ and ‘embracing distribution challenges’. Conclusions drawn from the findings were that producers have historically misunderstood audience needs and market volumes for their films, that profitability is achievable if one targets local markets modestly, that government support is critical but deficient in the South African environment, and that South African films need committed local distributors and exhibitors even before serious investment in Internet based distribution mechanisms. This study adds empirical data to an under researched field and contributes to understanding the nature of creative industries and their dynamics.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2011.
Keywords: Film industry; Filmmaking; Film value chain; South African film; Digital landscape; Film distribution; UCTD